G487 Does the department of health's community assessment tool (CAT) predict severe bronchiolitis in infants on admission?. (27th April 2016) - Shorthouse, L; Semple, M
Abstract : Introduction: The Department of Health developed CATs in 2008 to aid emergency healthcare staff during severe situations, when health seeking behaviours exceed capacity for the normal assessments. In the UK, bronchiolitis is the most common cause of infant hospital admissions and acute respiratory failure referrals to paediatric intensive care units. Evaluating a triage tool that could potentially help identify those severely ill infants who should be prioritised for assessment and may benefit from urgent care only available in hospitals is vital. Setting: Alder Hey NHS Foundation Trust, Liverpool, United Kingdom. The largest and busiest children's hospital in Europe and a lead referral centre for intensive care. Design: Retrospective case note review, October 2013–March 2014. CAT criterion data inferred from clinical findings and patient outcomes were single handedly extracted using the first recorded accident and emergency assessment. Participants: 106 infants ≤6 months (63 male, 43 female) from the local area (L1–L38 postcodes) admitted with bronchiolitis. Covariates: Paediatric CAT criteria: A 'Severe respiratory distress'; B 'Increased respiratory rate'; C 'Peripheral oxygen saturation ≤ 92% on breathing air and/or using supplemental oxygen'; D ' Respiratory exhaustion'; E 'Severe clinical dehydration or shock'; F 'Altered conscious level; and G 'Other clinical concern'. Outcomes: Oxygen; suction; intravenous fluids; intravenous antibiotics; nasogastric feeding, stay (≥ 48 h or ≥ 5 days); mechanical ventilation; and transfer to high dependency and/or intensive care. No mortality outcomes reported. Results and discussion: Based on multivariable analyses, each paediatric criterion (A-G) was relevant predicting a given outcome. Of note, criterion D 'Respiratory exhaustion' was the only criterion to independently predict the sickest infants requiring mechanical ventilation and transfer to high dependency and/or intensive care. This is a significant finding not obtained in previous work. Criterion G 'Other clinical concern' predicted the most outcomes supporting the importance of this subjective criterion. Conclusion: This study marks the first attempt to provide health professionals with a CAT evaluation specific to bronchiolitis. A strong relationship existed between the CAT and outcomes suggesting a potentially useful tool.